Developing Contextual Teaching and Learning-Based Interactive Handouts: An Investigation into Students' Mathematical Problem-Solving Performance - Yaomil Khoeriyah; Mochamad Abdul Basir; Hevy Risqi Maharani (Universitas Islam Sultan Agung, 2026)
This research aims to develop an interactive handout based on Contextual Teaching and Learning (CTL) that meets the criteria of validity, practicality, and effectiveness. The development of this instructional medium was intended to enhance students' mathematical problem-solving skills, specifically regarding the topic of similarity for seventh-grade students at SMP Islam Sultan Agung 1 Semarang. This study employed a Research and Development (R&D) approach using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. The interactive handout was constructed utilizing various digital platforms, including Canva, Quizizz, Liveworksheet, and Heyzine. Data collection techniques involved validation sheets from media, material, and language experts, teacher and student response questionnaires, and pretest-posttest instruments. Validation results demonstrated high levels of validity, reaching 95.38% from media experts, 98.26% from material experts, and 95.56% from language experts. Practicality tests based on teacher and student feedback achieved scores of 87.5% and 94.4%, respectively. Furthermore, effectiveness testing—measured through individual and classical mastery, as well as N-Gain scores—indicated an improvement in posttest results with an N-Gain value of 0.7067, categorized as high. Consequently, the CTL-based interactive handout is declared valid, practical, and effective in enhancing students' mathematical problem-solving skills. Keywords: Contextual teaching and learning (CTL), interactive handout, mathematical problem-solving.